Effectiveness of Telemedicine-Based Health Programs on Accessibility of Health Services in Remote Areas: A Case Study in Talaud Islands Regency, North Sulawesi - Harma, Harma (Magenta Journal De Healthymedi, 2024)
This study examines the effectiveness of telemedicine-based health programs in enhancing healthcare accessibility, patient satisfaction, and service quality in the Talaud Islands Regency, North Sulawesi. A quantitative research design was employed, utilizing descriptive and inferential statistical methods, including t-tests, regression analysis, and ANOVA, to analyse data from 300 respondents. The results show that telemedicine significantly reduces travel time, increases satisfaction, and improves access to both general and specialist healthcare services. Frequent telemedicine using correlates with higher patient satisfaction, particularly among older adults and those with higher education. The findings underscore the importance of digital literacy and education in the successful adoption of telemedicine in rural areas. This research contributes to the literature on telemedicine by addressing gaps related to its application in underserved regions, offering valuable insights for policymakers aiming to improve healthcare delivery in remote areas.